Combined Performance of Hill Cipher and Rivest Code 6 (Rc6) Algorithms in Image Security - Santoso, Heri; Rambe, Nia Sabrina; Suhardi, S (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2024)
Digital image files are a form of information that is accurate and reliable enough to describe something, so the level of authenticity of this information needs to be maintained. Especially when sent via the internet as in chat-based applications such as Facebook, WhatsApp, Instagram and other social media. To maintain the security and confidentiality of digital image/image information, it is necessary to have a technique called cryptography. Cryptography is a technique or algorithm for changing data or information to be different from the original information. For example, in everyday life, there is a result of a design order that is still in the development stage that needs to be shown to prospective buyers, a drawing file or documentation image file that is private and confidential, so it is important to pay attention to its security. This research will use the combined performance of the Hill Cipher and Rivest Code 6 cryptographic algorithms in securing image files. The results of the Hill Cipher and Rivest Code 6 cryptographic algorithm encryption are able to disguise the image during the encryption process. And can restore to the original image in the decryption process. So that the encrypted image is safer to send via the internet or social media.